Сучасні буклетні видання: класифікаційний аспект - Бойко, Анна С.; Boyko, А. S. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті розглянуто класифікаційну систему буклетів, проаналізовано критерії їх поділу й характерні особливості кожного різновиду. З’ясовано закономірності використання різних типів цих видань залежно від способу їх виготовлення, специфіки представленої інформації, мети розповсюдження тощо. The article considers the modern classification system booklets which are separated by several criteria: a model of the external form, formally - one aspect characteristics, distribution method, etc. Traced the relationship between the purpose of the booklet and the way it is printing performance and features of the internal (textual and illustrative) filling. Overall analysis was done on the efficiency, convenience and feasibility of various kinds of folding brochures, how to perform that play an important role in the formation of a holistic «image» advertising and informational publications: not only provide a comfortable, convenient location information on the sheet, but also attract the attention of potential customers with using non-standard (and sometimes vice versa − a practical and simple) form. In addition, a comparative description filed separate species booklet publications as the allocation of some of them is controversial. Research is complex, considering many aspects relating to the submission booklet quality product on the commercial and publishing markets.
Modern booklet edition: classification aspect
Keywords: іміджеві буклети; branding brochures; масові буклети; mass booklets; брошура; brochures; євробуклет; evrobuklet; лифлет; leaflet; фальц; rebate